From Imbalance to Inclusion: A Quantitative Study on Gender Participation Trends in Engineering and Architecture Education (AY 2020–2025) - Torres, Chrisjay S.; Narsico, Peter G. (Future Science / FSH-PH Publications, 2025)
Gender disparity remains a persistent issue in science, technology, engineering, and mathematics (STEM) education, particularly within engineering and architecture programs. While national and institutional initiatives have promoted inclusivity, localized assessments are essential to determine whether these efforts translate into sustained enrolment equity. This study employed a quantitative descriptive-comparative design, drawing on institutional freshman enrolment data from Academic Year (AY) 2020–2021 to AY 2024–2025. A total of 10,052 enrolment records were analyzed across multiple programs, disaggregated by gender. Descriptive statistics, visual trend analysis, and a chi-square test for trend were applied to assess gender participation over time. Findings revealed fluctuating patterns of female enrolment, with a notable increase in AY 2021–2022 (+52.1%) followed by modest growth and stabilization. While some programs (e.g., Architecture, Chemical Engineering) approached gender balance, others (e.g., Electrical and Mechanical Engineering) remained strongly male-dominated. The chi-square test indicated no statistically significant linear trend in female participation across years, χ²(1, N = 10,052) = 1.68, p = .196. Although there are signs of progress in selected programs, the lack of a significant trend suggests that institutional efforts toward gender inclusion have not yet resulted in consistent, system-wide change. The study highlights the need for program-specific interventions, continuous monitoring, and intentional policy implementation to address persistent enrolment disparities in STEM fields.